Financial statement analysis of Cergas Asli Sdn. Bhd. / Ramsis Anak William Agim... [et.al] - William Agim, Ramsis; Mambu, Vincent (2014)
The aim of this paper is to analyze the audited financial statements of Cergas Asli Sdn Bhd using financial ratios analysis to identify potential problem areas of the company. Horizontal analysis or trend analysis and cash flow analysis would also be done to support the findings of the financial ratio analysis. Based on the problem identified, structured interviews were conducted to further clarify on the problems areas identified from the financial ratio analysis, horizontal analysis and cash flow analysis.